2017
DOI: 10.3844/jcssp.2017.505.513
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Off of Frame-Rate and Resolution in Online Game Streaming

Abstract: Only limited research in the literature focused on assessment of different spatial and temporal resolutions. In addition, the field of synthetic video compression, such as video compression in game streaming, was the focus of only a few research papers. This paper will consider a wide range of synthetic video textures and motion speeds. The visual quality of the compressed video sequences is perceptually evaluated using the Double Stimulus Impairment Scale (DSIS) assessment metric. Extensive subjective viewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Furthermore, the results of an earlier study on synthetic videos used in video games [14] showed that H.264 produced superior quality compared to other codes. In a later study, [15] found that a lower frame rate can be used with low bit rates without degrading the gaming quality. However, this only works for low-motion sequences.…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the results of an earlier study on synthetic videos used in video games [14] showed that H.264 produced superior quality compared to other codes. In a later study, [15] found that a lower frame rate can be used with low bit rates without degrading the gaming quality. However, this only works for low-motion sequences.…”
Section: Related Workmentioning
confidence: 93%
“…Therefore, these components are monitored and researched to be improved. In [13][14][15][16][17][18][19][20], ideas to reduce the computational complexity of H.264/AVC and HEVC were proposed. The concepts in these works focused on two main steps and can be summarized into: motion estimation and mode decision.…”
Section: Related Workmentioning
confidence: 99%